A small-molecule SARS-CoV-2 inhibitor targeting the membrane protein - Ellen Van Damme; Pravien Abeywickrema; Yanting Yin; Jiexiong Xie; Sofie Jacobs; Mandeep Kaur Mann; Jordi Doijen; Robyn Miller; Madison Piassek; Simone Marsili; Murali Subramanian; Leah Gottlieb; et al. (Nature, 2025)
Abstract The membrane (M) protein of betacoronaviruses is well conserved and has a key role in viral assembly 1,2 . Here we describe the identification of JNJ-9676, a small-molecule inhibitor targeting the coronavirus M protein. JNJ-9676 demonstrates in vitro nanomolar antiviral activity against SARS-CoV-2, SARS-CoV and sarbecovirus strains from bat and pangolin zoonotic origin. Using cryogenic electron microscopy (cryo-EM), we determined a binding pocket of JNJ-9676 formed by the transmembrane domains of the M protein dimer. Compound binding stabilized the M protein dimer in an altered conformational state between its long and short forms, preventing the release of infectious virus. In a pre-exposure Syrian golden hamster model, JNJ-9676 (25 mg per kg twice per day) showed excellent efficacy, illustrated by a significant reduction in viral load and infectious virus in the lung by 3.5 and 4 log 10 -transformed RNA copies and 50% tissue culture infective dose (TCID 50 ) per mg lung, respectively. Histopathology scores at this dose were reduced to the baseline. In a post-exposure hamster model, JNJ-9676 was efficacious at 75 mg per kg twice per day even when added at 48 h after infection, when peak viral loads were observed. The M protein is an attractive antiviral target to block coronavirus replication, and JNJ-9676 represents an interesting chemical series towards identifying clinical candidates addressing the current and future coronavirus pandemics.